Student anger and aggressive behavior in school: an initial test of Agnew's macro-level strain theory - Brezina, Timothy (Journal of research in crime and delinquency, 2001)
Variation in criminal/delinquent behavior across communities, schools, and other social units is usually explained in terms of social disorganization and subcultural values. Agnew's macro-level strain theory MST, however, provides an additional explanation. MST contends that macro-level differences in crime and deviance can also be explained in terms of aggregate levels of anger and frustration. Following Agnew's recommendations, the authors conduct an initial school-level test of MST using data on aggressive student behavior from a national sample of public high schools. The results of the assessment lend partial support to the theory, showing that student-to-student conflict is partly a function of the level of anger in the student population. Other forms of aggressive student behavior, however, are not likewise affected. Nonetheless, the authors believe the findings are sufficiently promising to warrant further examination of MST, and they offer some suggestions in this regard